PENGEMBANGAN JALUR EKONOMI KREATIF DI KORIDOR JALAN TRANS SULAWESI BERBASIS SISTEM INFORMASI GEOGRAFIS - Fadhil Surur; Faridah Yusuf (Teknosains, 2019)
The development of Sulawesi trans road that has served the community from Makassar to Manado City through South Sulawesi Province to North Sulawesi has a positive impact on the regional economy. Spatially each region in the Trans Sulawesi road corridor has different creative economic potential. People traveling from Makassar City - Manado City through this pathway will be able to enjoy a variety of creative economic potentials, by obtaining information on creative economic products on offer. This study aims to identify the potential of creative economy, assess the potential of superior creative economy and map the potential of creative economy based on geographic information system based on the level of potential advantage possessed. Data were collected through google map observation, literature study until data searching through local planning documents. The results of data processing from descriptive analysis and scoring analysis are used as the basis of mapping based on geographic information system. The result of this research is a creative economic mapping product integrated with Trans Sulawesi road, where people can know the superior creative economic sub-sector offered by the area. On the different side of the media promotional units of micro, small and medium enterprises in offering creative economic products developed.